Potential Diagnostic and Prognostic Biomarkers of Circular RNAs for Lung Cancer in China. (25th August 2019) - Wang, Chengdi; Jiang, Yuting; Lei, Qian; Wu, Yangping; Shao, Jun; Pu, Dan; Li, Weimin
Abstract : Emerging evidence demonstrated that circular RNAs (circRNAs) were dysregulated in lung cancer, indicating that circRNAs might serve as novel diagnostic and prognostic biomarkers for lung cancer. However, the clinical value of circRNAs on lung cancer remains unclear. This study aimed to evaluate the efficiency of circRNAs in the diagnosis and prognosis for lung cancer in China. 2122 Chinese individuals were enrolled in this investigation for assessment of diagnostic value and examination of prognostic analysis. In the diagnostic analysis, the pooled sensitivity, specificity, PLR, NLR, DOR, and AUC of the sROC curve with their 95% CIs were 0.80 (95%CI: 0.74-0.84), 0.80 (95%CI: 0.73-0.86), 3.97 (95%CI: 2.80-5.62) and 0.26 (95%CI: 0.19-0.34), 15.51 (95%CI: 8.76-24.47), and 0.85 (95%CI: 0.82-0.88), respectively. As for the prognostic power of circRNAs, lung cancer patients with higher expression levels of circRNAs tend to possess lower overall survival with the overall pooled HR (1.70, 95%CI: 1.26-2.29). Furthermore, in stratified analysis, upregulated and downregulated circRNAs were manifested to exert significant effects on prognosis with HR values of 2.17 (95%CI: 1.74-2.72) and 0.52 (95%CI: 0.34-0.80). This study validates that circRNAs are promising diagnostic and predictive biomarkers for lung cancer patients in China.